Assessing the Utility of Mental Health First Aid Training for Physician Assistant Students. Issue 4 (December 2022) - Forbes, Jennifer; Noller, Diana T.; Henriquez, Madeleine; Scantamburlo, Sarah; Ward, Ian; Lee, Hwal
Abstract : Introduction: Physician assistant (PA) students are at increased risk for anxiety and depression compared with the general population. The demands of studying medicine can contribute to a decline in mental health, which may impede a student's ability to progress in his or her PA program. Mental Health First Aid (MHFA) is one strategy that can be used to increase mental health literacy, promote help-seeking behavior, reduce stigma, and improve confidence in providing help to individuals showing signs of a mental health disorder. The aim of this outcomes assessment was to assess PA students' satisfaction with the MHFA course and their posttraining confidence in using the skills learned. Methods: Participants were PA students (N = 435) across 9 PA programs in their didactic year of training who had completed an MHFA course through the PA Foundation's Mental Health Outreach Fellowship. MHFA postcourse evaluations, completed by the PA students, were analyzed to determine PA students' satisfaction with the course and their posttraining confidence in using the skills learned to help both themselves as well as the general population. Results: The mean of the MHFA course evaluation items corresponding to satisfaction with the course was 4.82 (maximum score of 5), and the mean of the items corresponding to posttraining confidence in using the skills learned was 4.74 (maximum score of 5). When asked, "Would you recommend this course to others?" 99.3% of the PA students trained in MHFA answered "yes, " indicating a high level of satisfaction with the training they had received. DIscussion: PA students who received MHFA training from the PA Foundation's Mental Health Outreach fellows showed high levels of satisfaction with the MHFA course and posttraining confidence in using the skills learned.